The Scientific Study of Personal Wisdom
XIV, 356 p. 13 illus.
Keywords: The rich and diverse contributions to this volume span a wide variety of disciplines, from psychology and philosophy to neuroscience, by some of the most influential scholars in the emerging science of personal wisdom. As such, it is a collection of essential readings and the first publication to integrate both the spiritual and pragmatic dimensions of personal wisdom. The content of the book goes beyond speculative theory to present a wealth of scientific research currently under way in this expanding field. It also describes numerous promising methods now being deployed in the quest for scientific knowledge of the elusive, yet critical, phenomenon of personal wisdom. The book is an excellent introduction to the field for novice researchers as well as a stimulating and enlightening resource for established experts. Its broad appeal makes it a vital addition to the libraries of academics and practitioners in many disciplines, from developmental psychology to gerontology, and from philosophy to contemplative religious traditions such as Buddhism.